2006
DOI: 10.1521/suli.2006.36.4.467
|View full text |Cite
|
Sign up to set email alerts
|

Social Work Education in Suicide Intervention and Prevention: An Unmet Need?

Abstract: Research shows that social work graduate programs offer little education in suicide prevention and intervention, yet social workers' experiences and attitudes regarding suicide education are unknown. This Web-based survey of 598 social workers found that almost all respondents had worked with at least one suicidal client, but most received little, if any, training in suicide prevention or intervention while in graduate school. Respondents largely viewed their social work program's training in suicide preventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(90 citation statements)
references
References 33 publications
1
87
1
1
Order By: Relevance
“…Despite the regularity with which mental health professionals encounter suicidal clients (Feldman & Freedenthal, ; Kleespies, Penk, & Forsyth, ), practitioners’ formal graduate training in suicide risk assessment and management has been shown to be limited and, in many cases, inadequate (Cramer, Johnson, McLaughlin, Rausch, & Conroy, ). For example, Bongar and Harmatz () reported that only 35% of clinical psychology doctoral programs offered formal instruction related to suicide.…”
Section: Obstacles To Service Provisionmentioning
confidence: 99%
“…Despite the regularity with which mental health professionals encounter suicidal clients (Feldman & Freedenthal, ; Kleespies, Penk, & Forsyth, ), practitioners’ formal graduate training in suicide risk assessment and management has been shown to be limited and, in many cases, inadequate (Cramer, Johnson, McLaughlin, Rausch, & Conroy, ). For example, Bongar and Harmatz () reported that only 35% of clinical psychology doctoral programs offered formal instruction related to suicide.…”
Section: Obstacles To Service Provisionmentioning
confidence: 99%
“…A survey of psychologists‐in‐training found that 97% of respondents had provided care to at least one patient (and often several) with some form of suicidal behavior or suicidal ideation during their training (Kleespies et al., 1993). In addition, social workers encounter suicidal patients on a regular basis, with 87% of social workers in a random nationwide sample reporting that they had worked with a suicidal patient within the past year (Feldman & Freedenthal, 2006). Other research has found that 55% of clinical social workers reported that at least one of their patients had attempted suicide during their professional careers (Sanders, Jacobson, & Ting, 2008).…”
Section: The Incidence Of Patient Suicidal Behavior In Clinical Practicementioning
confidence: 99%
“…Training has been similarly sporadic among social work training programs. Less than 25% of a national sample of social workers reported receiving any training in suicide prevention, with a majority of the respondents reporting that their training had been inadequate (Feldman & Freedenthal, 2006). Faculty and deans–directors of graduate social work programs reported that most students receive 4 hours or fewer of suicide‐related education (Ruth et al., 2009).…”
Section: The Prevalence Of Training In Suicide Risk Assessment and Mamentioning
confidence: 99%
See 1 more Smart Citation
“…The only national survey on suicide risk assessment and management included a sample of 598 practicing social workers, 93% of whom reported working with suicidal clients (Feldman & Freedenthal, 2006). 67.4% of this sample indicated that their training to assess, manage, and treat suicidal clients had been inadequate.…”
mentioning
confidence: 99%